The Influence of Financial Literacy and the Understanding of Tri Pantangan on the Management of Personal Financial in Accounting Students - Wardani, Dewi Kusuma; Nurhayati, Santi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Financial management is a method to manage owned funds related to individual responsibility in managing finances. The young generation is currently required to have the skills and knowledge to manage their personal finances effectively. As part of the young generation, students must have knowledge of the personal financial field from an early age. Therefore, this study aims to examine whether of financial literacy and the understanding of tri pantangan (Tamansiswa’s teaching) have significant influence on managing students' personal finances. The method used in this study was quantitative method. Samples used in this study were Accounting students in the Faculty of Economics Universitas Sarjanawiyata Tamansiswa Yogyakarta. The sampling technique used convenience sampling. The samples used were 104 respondents. This study used primary data by disseminating questionnaires in the form of Google Form links via Whatsapp and Telegram applications. The level of research significance used 0.5 or 5%. Testing was conducted using the IBM SPSS Statistic 20 program. Data analysis in this study used multiple regression analysis. The results of the study showed that financial literacy had a significant influence on student financial management, while there was no influence of the understanding of tri pantangan Tamansiswa on student financial management.